High‐efficiency separation of oil sands using ChCl‐based deep eutectic solvents. (4th October 2022) - Yuan, Wei; Zhao, Yidi; Zhang, Yu; Ma, Shanshan; Sun, Yinlu
Abstract: Deep eutectic solvents (DESs) are a kind of potential lixiviant for extraction processing. Unlike conventional ionic liquids (ILs), DESs are relatively cheap and environmentally friendly. Herein, three different ChCl‐based DESs, namely, choline chloride/urea, choline chloride/ethylene glycol, as well as choline chloride/propandioic acid, were synthesized and used to enhance bitumen recovery from oil sand by petroleum ether extraction. The results showed a multiphase system formed after mixing the components at 25°C, consisting of sands and clays, a DES layer, and a petroleum ether layer containing the bitumen. These DESs were immiscible with bitumen or petroleum ether. Coupled with a density difference, a clear phase separation was presented between the bitumen–petroleum ether mixture and DES. The DES functioned as a separating agent, keeping the petroleum ether–bitumen mixture and spent sand apart from each other. The results showed that the bitumen recovery was increased by 12% compared with that without the DESs. We deduced that the enhancement in the separation may result from the reduction of adhesion between bitumen and sand by the DESs. The ChCl‐based DESs and petroleum ether could be readily recycled to reduce industrial costs. After 10 cycles, the bitumen recovery remained above 86%.